Evolution of photovoltaic solar modules dark properties after exposition to electrical reverse stress current inducing thermal effect. Issue 2 (29th April 2014) - Sidawi, Jihad; Zaraket, Carine; Habchi, Roland; Bassil, Nathalie; Salame, Chafic; Aillerie, Michel; Charles, Jean-Pierre
Abstract : Purpose: – The purpose of this paper is to investigate the dark properties as a function of reverse current induced defects. Dark characteristics of solar modules are very essential in the understanding the functioning of these devices. Design/methodology/approach: – Reverse currents were applied on the photovoltaic (PV) modules to create defects. At several time intervals, dark characteristics along with surface temperature were measured. Findings: – Current-voltage (I-V) and capacitance-voltage (C-V) characteristics furnished valuable data and threshold values for reverse currents. Maximum module surface temperatures were directly related to each of the induced reverse currents and to the amount of leakage current. Microstructural damages, in the form of hot spots and overheating, are linked to reverse current effects. Experimental evidence showed that different levels of reverse currents are a major degrading factor of the performance of solar cells and modules. Originality/value: – These results give a reliable method to predict most of the essential characteristics of a silicon solar cell or a module. Similar test could help predict the amount of degradation or even the failure of PV modules.